The Concept Of Culture In English Philosophy - Yasavievna, Shigabutdinova Dina (The journal of contemporary issues in business and government, 2021)
This paper argues the frequency of the usage of the culture in the English philosophy as, in effect cultural stratum, with heuristic value. There is a generally sound rule which supports conditions in appropriate contexts, though these rules are enhanced with the fact that the notion of culture has underwent rapid transformation in the beginning of the 21st century.